SYNERGY OF STORE ATMOSPHERE AND BRAND IMAGE: ANALYSIS OF ITS INFLUENCE ON CONSUMER PURCHASING DECISIONS AT SOCIOLLA JAMBI CITY - Pangestu, Mira Gustiana; Fahdillah, Yosi; Sabrina, Hanan Laras (Journal of Business Studies and Management Review, 2024)
The changing landscape of e-commerce businesses is the result of rapid technological advancements and changes in customer behavior. One of the largest beauty e-commerce businesses in Indonesia, PT Socio Bella, also known as Sociolla, is a platform that faces intense competition to develop and retain its online consumers to offline consumers in stores. This study aims to see how the influence of store atmosphere and brand image on consumer purchasing decisions partially and simultaneously. This study uses quantitative research methodology with an associative approach to see the effect of store atmosphere and brand image on purchasing decisions at Sociolla in Jambi City. The population used in this study were consumers who had made purchases or visited Sociolla in Jambi City while the sampling method used in the process was purposive sampling which involved a total of 100 respondents using the Lemeshow formula. The results showed that at Sociolla Jambi City, store atmosphere has a significant and positive influence on purchasing decisions and brand image has a significant and positive influence on purchasing decisions while both have a simultaneous effect on consumer purchasing decisions. So it can be concluded that these two factors go hand in hand with the emergence of consumer purchasing decisions at Sociolla Jambi City.